A Workforce Value Chain Analysis In High Tech Multinational Corporations' Electronic Manufacturing In Penang - See, Lay Hoon (2010)
The present research aims to explore the depth in the pioneer MNC investment company and to investigate on workforce value chain for sustainability and survival. Penyelidikan ini bertujuan untuk meneroka syarikat pelaburan MNC peneraju dan menyelidik rantaian nilai tenaga kerjanya untuk kelestarian dan kemandirian syarikat.